1972
DOI: 10.1037/h0032071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of within-category spacing on free recall.

Abstract: The effects of within-category spacing (WCS) on free recall of categorized lists were analyzed. WCS was varied from 0 to 13 for uncued and categorycued recall tasks in unmixed-and mixed-list designs. Contrary to previous experiments which found recall with blocked spacing always superior to recall with "random" spacings, these experiments found that total recall was a function of two independent factors: (a) recall of category names or category representation which is an increasing linear function over WCS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…However, most of the prior work on blocked-random effects has not accounted for this influence (e.g. Cofer et al 1966; D’Agostino 1969; Borges and Mandler 1972). Through bootstrapping techniques, it is possible to estimate the amount of semantic organization due to temporal clustering (Morton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the prior work on blocked-random effects has not accounted for this influence (e.g. Cofer et al 1966; D’Agostino 1969; Borges and Mandler 1972). Through bootstrapping techniques, it is possible to estimate the amount of semantic organization due to temporal clustering (Morton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is a particularly critical issue when examining how semantic organization is influenced by manipulations of presentation order (e.g. Glanzer 1969; Borges and Mandler 1972; for a review, see Puff 1974). Morton et al (2013) demonstrated a permutation-based technique that can be used to estimate the baseline level of semantic organization expected in the presence of temporal organization.…”
Section: Introductionmentioning
confidence: 99%
“…Participants provided JOLs immediately following each item in the list and then completed a free recall test. Although blocking category exemplars at study usually leads to better recall than spacing them over the list (e.g., Dallett, 1964; but see Borges & Mandler, 1972) categorized items were nevertheless expected to be recalled better than unrelated items, and big categories were expected to be recalled better than small categories. The goal of Experiment 1 was to determine whether participants could accurately predict how category size would affect free recall performance.…”
Section: Monitoring Relatednessmentioning
confidence: 99%
“…It has been observed, however, that category recall is superior following random presentation when compared to blocked presentation (Borges & Mandler, 1972;Hartley, 1974;Lewis, 1974). Since a demonstration of cueing requires a difference between cued and noncued subjects treated otherwise identically, it is possible that providing intralist cues to random presentation groups has been ineffective largely because these groups had fewer inaccessible categories than corresponding blocked presentation groups.…”
mentioning
confidence: 98%